Impact of Abdominal Obesity on CVD and Diabetes - Mosley, Mary (MD Conference Express, 2013)
Obesity is an inflammatory process, and as visceral adipose tissue (VAT) increases, inflammation increases. As the components of metabolic syndrome increase, inflammation increases, as shown by increases in C-reactive protein (CRP) in the Women's Health Study [Ridker PM et al. Circulation 2003]. Additionally, this article discusses the role of epicardial and intrathoracic fat with cardiovascular (CV) risk factors, and the association between low levels of high-density lipoprotein cholesterol (HDL-C; <60 mg/dL) and increased hazard of coronary heart disease, stroke, and CV events.